Estimating the Period Prevalence of Publicly Funded Abortion to Space Live Births, 1999 to 2014 - James Studnicki; John W. Fisher; Tessa Longbons; David C. Reardon; Christopher Craver; Donna J. Harrison (SAGE Publishing, 2021)
Introduction/Objectives: Although a majority of women who have an abortion report having 1 or more children, there is no published research on the number of abortions which occur between live births, after a first child but before the last. The objectives of this research, therefore, were to estimate the period prevalence of an induced abortion separating live births in a population of Medicaid eligible enrollees and to identify the characteristics of enrollees significantly associated with the use of abortion to enable child spacing. Methods: A retrospective, cross-sectional, longitudinal analysis of the pregnancy outcome sequences of eligible enrollees over age 13 from the 17 states where Medicaid included coverage of all abortions, with at least one identifiable pregnancy outcome between 1999 and 2014. Eligibles with a defined sequence of birth-abortion-birth within up to 5 consecutive pregnancies were identified to estimate the number of eligibles who could have practiced birth spacing by abortion. Logistic regression was applied to identify the significant predictor variables of the birth-abortion-birth sequence. Results: There were 50 012 (1.02%) of 4 875 511 Medicaid eligible enrollees exhibited a birth-abortion-birth sequence. Eligibles with the birth-abortion-birth sequence are more likely to be Black than White (OR 2.641, CL 2.581-2.702), less likely to be Hispanic than White (OR 0.667, CL 0.648-0.687), and more likely to have received contraceptive counseling (OR 1.14, CL 1.118-1.163). Increases in months of Medicaid eligibility (OR 1.004, CL 1.003-1.004) and months from first pregnancy to second live birth (OR 1.015, CL 1.015-1.016) are associated with the likelihood of undergoing live births separated by one or more induced abortions. Increases in the age at first pregnancy are associated with a decreased likelihood of the birth-abortion-birth sequence (OR 0.962, CL 0.959-0.964). Conclusion: Birth spacing via abortion is uncommon among a low-income population for whom the financial barriers to abortion are somewhat alleviated.